PEMBERDAYAAN PEREMPUAN DESA SUNGKAP BERBASIS SORGHUM VALUE ADDED SEBAGAI BAHAN PANGAN ALTERNATIF DALAM MENCIPTAKAN RUMAH TANGGA BERDAYA EKONOMI - ANGGRAENI YUNITA ,; RULYANTI SUSI WARDHANI,; ERITA ROSALINA,; NUR AHMAD RICKY RUDIYANTO,; CHRISTIANINGRUM, (KRIDA CENDEKIA, 2021)
The paradigm shift regarding the source of community income raises its own problems. Currently, the residents of S disclosed village still rely on rubber and pepper commodities as their main source of livelihood. Meanwhile, the current problem is that the low price of pepper and rubber is the main problem for farmers because the selling of rubber and pepper cannot cover production costs. The village government of Surkan has empowered residents to cultivate horticultural crops in the form of chilies, eggplant and typical Bangka vegetables such as alar taro. However, in order to contribute to increasing Village Original Income and improving the residents' economy, the discourse on sorghum cultivation can be an alternative for people with food resilience. In addition, the women of S disclosed village still cannot be said to be economically empowered in helping the head of the household to prosper the family due to the lack of training and assistance for housewives in improving skills and abilities that can be used as an effort to improve family welfare. Partners, in this case the Village Head and PKK Chair, hope that there will be synergy between the Provincial Government and Regency Governments to support several sectors such as capital, agricultural technology, seeds, fertilizers and marketing strategies needed so that the community is ready to make efforts to cultivate shorgum plants and create added value in the form of prepared sorghum plant